SA-MEAS: Sympy-based automated mathematical equations analysis and solver - Ali, Amjad; Khusro, Shah (SoftwareX, 2024)
Students with blindness and visual disabilities encounter challenges learning mathematics, particularly mathematical equations (MEs), which contributes to their underrepresentation in STEM fields. MEs are complex because they have a two-dimensional structure, which makes them difficult to access. In addition, inconsistencies in Braille codes across regions, lack of collaborative math platforms, and a lack of accessible mathematics literature exacerbate their difficulties. Technology and tools currently available limit MEs analysis and solution. This study proposes a mathematical equation analysis and solving software application called SA-MEAS (Sympy-based Automated Mathematical Equation Analysis and Solver) for mathematical linear and quadratic equations and expressions. The proposed solution provides a quick overview and solutions for MEs. The overview provides terms, factors, variables and constants, types of equations, structure and a detailed summary of MEs. Also, it provides correct solutions. Students correlate the summary and solution and build a mental model of the MEs. To develop this application a Python symbolic mathematics library (sympy) was utilized to automate MEs analysis and solution. Similarly, a speech synthesis library verbally summarized the analysis and solution. Furthermore, a Python speech recognition library was used for interactive communication. Finally, a user-friendly interface was designed by utilizing the Tkinter library. The proposed software was empirically evaluated with 32 blind and visually impaired students, and significant improvements were found in math accessibility and learning.